2014
DOI: 10.1038/jcbfm.2014.201
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Fails to Disrupt White Matter Integrity in Young Or Aged Fisher (F44) Cyp1a1Ren2 Transgenic Rats

Abstract: Hypertension is linked with an increased risk of white matter hyperintensities; however, recent findings have questioned this association. We examined whether hypertension and additional cerebrovascular risk factors impacted on white matter integrity in an inducible hypertensive rat. No white matter hyperintensities were observed on magnetic resonance imaging either alone or in conjunction with ageing and high-fat diet. Aged hypertensive rats that were fed a high-fat diet had moderately reduced fractional anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We found that the volume index of GM/TIV gradually decreased, whereas the WM/TIV increased from 10 to 80 weeks in both groups. One preclinical study on hypertension and white matter disruption in inducible hypertensive rats reported that hypertension fails to disrupt white matter integrity in young or aged rats, which is consistent with our findings ( Holland et al, 2015 ). Regional brain changes in aging adults with hypertension have confirmed white matter injury ( Sabisz et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the volume index of GM/TIV gradually decreased, whereas the WM/TIV increased from 10 to 80 weeks in both groups. One preclinical study on hypertension and white matter disruption in inducible hypertensive rats reported that hypertension fails to disrupt white matter integrity in young or aged rats, which is consistent with our findings ( Holland et al, 2015 ). Regional brain changes in aging adults with hypertension have confirmed white matter injury ( Sabisz et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Recent evidence from animal models also suggest that hypertension is not the key driver of white matter changes. 36,37 Our results show that some radiologic, pathologic, and cognitive features of human SVD can be recapitulated in a mouse model by common carotid stenosis. Our findings also provide evidence that hypoperfusion may precipitate SVD-like disease culminating in a progressive brain and gliovascular pathology.…”
Section: Discussionmentioning
confidence: 63%
“…Long‐term induction of hypertension in aged Cyp1a1‐Ren2 rats with a high‐fat diet have been shown to have microstructural alterations but no white matter lesions (Holland et al. ). These modest changes, as well as the modest changes seen in our work, are an indication that this model could be beneficial in observing the mechanisms at play in the human condition.…”
Section: Discussionmentioning
confidence: 99%